Changes in the content and influence factors of α-solanine in potato during storage - Jianquan Kan, Xiaolong Chen (Emirates Journal of Food and Agriculture, 2018)
This paper presents a study on storage of three species of potato: Ruby, Black Beauty and Favorita. By using of high-performance liquid chromatography, the study investigated their variation pattern of α-solanine in different storage conditions including greenhouse with fluorescent lamp, greenhouse without fluorescent lamp, cold storage (4°C) and shaded, machine-damaged and shaded, and machine-damaged with fluorescent lamp. The experimental results showed that the content of α-solanine in Ruby is higher than Favorita and Black Beauty under the same conditions; and the content of α-solanine in peels is generally higher than tubers among the same specie; the following storage conditions influenced the content of α-solanine in potatoes to varying degrees: machine-damaged with fluorescent lamp > machine-damaged and shaded > greenhouse with fluorescent lamp > greenhouse without fluorescent lamp > cold storage (4°C) and shaded; and the content of α-solanine presented a trend of increasing firstly and then decreasing under the greenhouse with fluorescent lamp, greenhouse without fluorescent lamp, machine-damaged and shaded and machine-damaged with fluorescent lamp, but it nearly remains unchanged in the cold storage (4°C) and shaded. This study provides a useful reference to the proper storage of potatoes.